Aaptamine Enhanced Doxorubicin Activity on B-Cell Lymphoma 2 (Bcl-2): A Multi-Structural Molecular Docking Study - Setiawansyah, Arif; Susanti, Gita; Alrayan, Reza; Hadi, Ismanurrahman; Ikhlas Arsul, Muhammad; Luthfiana, Dewi; Wismayani, Leni; Hidayati, Nurul (Ad-Dawaa’ Journal of Pharmaceutical Sciences, 2024)
Doxorubicin, a widely used chemotherapeutic agent, targets Bcl-2, but its efficacy can be limited by drug resistance. Its combination with natural derived compound can be a therapeutic approach to overcome this problem. This study aimed to investigate the molecular interactions and binding affinities of aaptamine and doxorubicin with Bcl-2 using molecular docking simulations, and to evaluate the potential synergistic effects of their combination. Molecular docking studies were performed to predict the binding modes and affinities of aaptamine and doxorubicin along with their combination to Bcl-2. Molecular docking simulation results showed that aaptamine binds to the BH3 binding groove of Bcl-2, forming key interactions with residues like Asp70, Tyr67, Phe112 and Glu111. Aaptamine stabilized the binding of doxorubicin to Bcl-2 through hydrophobic bonding and van der Waals interactions, resulting in enhanced binding affinity. The combination of aaptamine and doxorubicin exhibits synergistic anticancer effects by enhancing the binding affinity of doxorubicin to Bcl-2. Molecular docking simulations provided insights into the stabilizing interactions between aaptamine, doxorubicin, and Bcl-2, suggesting a potential strategy for overcoming Bcl-2-mediated drug resistance in cancer. However, further in vitro investigation is needed to be implemented.